2021
DOI: 10.1016/j.jaerosci.2021.105769
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of prolonged airborne dispersion of novel coronavirus-laden droplets

Abstract: We have performed highly accurate numerical simulations to investigate prolonged dispersion of novel coronavirus-laden droplets in classroom air. Approximately 10,900 virus-laden droplets were released into the air by a teacher coughing and tracked for 90 min by numerical simulations. The teacher was standing in front of multiple students in a classroom. To estimate viral transmission to the students, we considered the features of the novel coronavirus, such as the virus half-life. The simulation results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…To investigate realistic droplet motions, we use the frequency distribution of the diameter of the droplets expelled from the mouth by coughing shown in Figure 5A. This particle distribution was used in the authors' previous study 12 . Figure 5B shows the time variation of cough‐generated droplet radius r based on Equation (10) with a minimum radius.…”
Section: Numerical Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate realistic droplet motions, we use the frequency distribution of the diameter of the droplets expelled from the mouth by coughing shown in Figure 5A. This particle distribution was used in the authors' previous study 12 . Figure 5B shows the time variation of cough‐generated droplet radius r based on Equation (10) with a minimum radius.…”
Section: Numerical Approachmentioning
confidence: 99%
“…Figure 5B shows the time variation of cough‐generated droplet radius r based on Equation (10) with a minimum radius. The total number of droplet particles expelled from the mouth in a cough is 10 900 12 . The number of droplets generated per unit time is proportional to the flow rate.…”
Section: Numerical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The extraction of particles in a room can be based on thresholds defined in different standards, and in one study on outpatient clinic rooms, it was found that lower than standard air changes per hour could lead to increased risks of viral spread ( King et al., 2021 ). 15% of air-borne virus-laden droplets remained in a classroom study even after 90 min due to a low ventilation rate ( Yamakawa, Kitagawa, Ogura, Chung, & Kim, 2021 ).…”
Section: Introductionmentioning
confidence: 99%